Música y Trabajo Organizaciones gremiales de músicos en Chile, 1893-1940 - Karmy, Eileen (Ariadna Ediciones, 2021)
This book tells a history of music in Chile from the perspective of labor, which has not been sufficiently explored until now. Instead of prioritizing the work of art, the author puts the work of the musicians and their union organizations at the center. She builds the story from various sources, many of them unpublished and written by the musicians who worked between 1893 and 1940, in Valparaíso, Chile.